PARAPLEGIA AND TRACK CYCLING – CASE STUDY ABOUT THE EFFECTS OF A 10 WEEK TRAINING ON A PARA-ATHLETE PERFORMANCE AT THE 1KM TIME TRIAL (Fiep Bulletin - online, 2012)
A major challenge posed by the CP would be the predominant use of the lower limbs, even among athletes who have been affected by spinal cord injuries. Paraplegia is a type of spinal cord injury, traumatic or ischemic, which drastically reduces the motor command from the pelvis and lower limbs, Objective: A case study on the effects of ten weeks of training in peak power (PP ), maximum speed (Vmax) and fatigue index (FI) of these variables during the simulation of the 1000m Time Trial. Sample: A paraplegic individual ((33 years old,75,5kg,1,79m)  with previous experience in training in CP. Methods: To perform three assessments (initial, intermediate and final) that simulates the1000m  time trial, during ten weeks of specific training for speed development. We used a power meter SRM ® for the continuous reading of the time, distance, speed and power. Results: The intermediate evaluation of PP had lower than baseline (202 and 205W) but the intermediate evaluation of IF was lower (49.5 and 53.2%). The final evaluation showed the highest PP (216W), with the IF similar to the initial (53.2%). The Vmax was increased progressively during the three assessments (28.8, 29.4 and 30.4 km / h). The IF of velocity was similar in the first two assessments (11.8 and 11.9%) and higher in final assessment (13.2%), but the latter was recorded at the shortest time to complete 1000 m. Conclusion: The proposed training program was able to improve an athlete’s performance in this study. Although paraplegia determine unique features, athletes and coaches should be encouraged to direct training specifically to sport.
Keywords: Paraplegia; Track Cycling; Power.